Massively HIV-1-infected macrophages exhibit a severely hampered ability to differentiate into osteoclasts - Sviercz, Franco A.; Jarmoluk, Patricio; Cevallos, Cintia G.; López, Cynthia A. M.; Freiberger, Rosa N.; Guano, Alex; Adamczyk, Alan; Ostrowski, Matías; Delpino, M. Victoria; Quarleri, Jorge (Frontiers in Immunology, 2023)
Osteoclasts play a crucial role in bone resorption, and impairment of their differentiation can have significant implications for bone density, especially in individuals with HIV who may be at risk of altered bone health. In this study, we investigated the effects of HIV infection on osteoclast differentiation using monocyte-derived macrophages as precursors. We found that when precursors are rapidly, massively, and productively infected with HIV, osteoclastogenesis is severely impaired, affecting cellular adhesion, cathepsin K expression, and resorptive activity. Although the macrophages exhibited an M2-like profile that was not altered by HIV infection, the production of IL-1β increased earlier with the high inoculum, concurrent with the receptor activator for nuclear factor κ B ligand (RANK-L) and suppressing the production of osteoclasts. Besides, we observed that the expression of co-receptor CCR5, as well as the tetraspanins CD9 and CD81, increased after infection with the high inoculum, which accompanied deficient osteoclastogenesis. Furthermore, a massive HIV infection of osteoclast precursors affected the transcriptional levels of key factors for osteoclastogenesis, such as RANK, NFATc1, and DC-STAMP. Our findings suggest that the effects of HIV infection on osteoclast precursors depend on the size of the inoculum and the kinetics of viral replication. Understanding these mechanisms could lead to the development of new strategies to prevent or treat bone disorders in people with HIV.